PENGEMBANGAN ASESMEN FORMATIF BERBASIS WORDWALL PADA MATA PELAJARAN PEMDIDIKAN PANCASILA KELAS III SD NEGERI 39 PONTIANAK UTARA - Baita, Pia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
The formative assessment evaluation system for learning that still uses common methods such as doing assignments in exercise books and then being scored can make students easily bored, tired, and unmotivated in following the learning process. There needs to be innovation in formative assessment that can support and optimize the learning process. The use of technology in the development of formative assessment can be an effective and efficient means of measuring student competency achievement. This study uses the research and development (R&D) method and applies the stages of the ADDIE development model. Data collection techniques in this study were interviews and questionnaires. The subjects in this study were teachers and students of class III A of SD Negeri 39 Pontianak Utara. The results of the validation by material experts obtained an average score of 96,5% with the criteria "Very Valid" and the results of the validation by media experts obtained an average score of 90,49% with the criteria "Very Valid". The results of teacher responses to wordwall-based formative assessments obtained an average score of 95% with the criteria of "Very Good" and the results of student responses to wordwall-based formative assessments obtained an average score of 94,5% with the criteria of "Very Good". Based on the results of the study, it can be concluded that wordwallbased formative assessments in Pancasila education subjects are feasible to use and have been tested for validity and response levels.